Rhododendron longipedicellatum (Ericaceae), a new species from Southeastern Yunnan, China - Cai, Lei; Neilsen, Jens; Dao, Zhi-Ling; Ma, Yong-Peng (Phytotaxa, 2016)
A new species of Rhododendron (Ericaceae) in sect. Vireya subsect. Pseudovireya from Malipo County, Southeast Yunnan, China, R. longipedicellatum, is described and illustrated. The new species is most similar to R. rushforthii but differs in its arrangement of leaves, the shape and color of the lamina, length of the petiole and the size of the calyx lobes. It also resembles R. trancongii and R. Datiandingense, but differs in its color and shape of the lamina, the leaf apex, lengths of the petiole, pedicel and stamens, and the indumentum of the ovary.